Changing trend in mortality rate of multiple myeloma after introduction of novel agents: A population‐based study. Issue 11 (6th July 2020) - Usui, Yoshiaki; Ito, Hidemi; Koyanagi, Yuriko; Shibata, Akiko; Matsuda, Tomohiro; Katanoda, Kota; Maeda, Yoshinobu; Matsuo, Keitaro
Abstract: Previously, the main treatment for multiple myeloma (MM) was cytotoxic chemotherapies, including autologous stem‐cell transplantation (ASCT), but survival benefit in the elderly was limited. More recently, clinical trials and practical experience with novel agents with superior efficacy have shown improved survival, including in the elderly. However, this improvement cannot be simply interpreted as a decline in mortality rate that is an important public health measure of progress against cancer. Here, we assessed the trends in mortality rates of MM in parallel with incidence rates in Japan and the U.S. We used national mortality data and population‐based cancer registry data in both countries from 1995 to 2015, during which 74 972 patients in Japan and 229 290 patients in the U.S. died of MM. Trends in mortality and incidence rates were characterized using joinpoint regression analysis. Despite upward trends in incidence, mortality rates showed a significant decrement after 2005 in Japan, with an annual percent change [APC (95% confidence interval)] of −2.5% (−2.9% to −2.1%), and after 2002 in the U.S., with an APC of −2.0% (−2.6% to −1.5%). In both countries, the change in mortality trend coincided with the introduction of the novel agents. Moreover, improvements in mortality were particularly large in patients aged 70 to 79 years, who cannot receive ASCT. Our results indicate that the benefits of novel agents for MM are appreciable at the population level and may encourage further development of novel agents for malignancies that can be widely applied to the patients. What's new?: Mortality rate is a key public health measure of progress against cancer and is sometimes markedly impacted by the approval of novel anticancer interventions. Here, the authors evaluated mortality and incidence rates of multiple myeloma (MM) in Japan and the United States, searching for trends associated with new therapeutic interventions. Their analyses show that mortality rates of MM decreased significantly after the introduction of novel therapies in the early 2000s, despite increasing trends in MM incidence rates in both countries. Mortality rates improved considerably among older patients, ages 70 to 79, who are unable to undergo autologous stem‐cell transplantation.